Fundamentals of Entrepreneurship (ENT300) : Tadika and Taska Sang Kancil / Connielia Tennent … [et al.] - Tennent, Connielia; Nazarudin, Liyana Batrisyia; Mohamad Iskander, Nurul Harisha; Mahdi @ Salleh, Sarmiza; Husaini Syied Malek Faisal, Syied Hamiduddin; Damian, Vanaessa Evangelista (2019)
Tadika and Taska Sang Kancil has been recognized by most parents especially those who lived nearby Petra Jaya area. This kindergarten offers and provides the services of teaching and taking care of the children. The major problem faced by this business is that the economy now is bad or unstable and the government is not really helping such sole-proprietorship business. As for the economy, some parents could not afford to pay the monthly fee. Tadika and Taska Sang Kancil sets a higher fee compared to other kindergartens. But, the fee sets by Tadika and Taska Sang Kancil shows the quality of education that is provided is way much more better than other kindergarten.